Evolution of camel CYP2E1 and its associated power of binding toxic industrial chemicals and drugs. (October 2016) - Kandeel, Mahmoud; Altaher, Abdullah; Kitade, Yukio; Abdelaziz, Magdi; Alnazawi, Mohamed; Elshazli, Kamal
Graphical abstract: Highlights: CYP2E1 is a molecular sieve for detoxifying small molecules. Camel CYP2E1 showed higher evolution rate compared with human and other test organisms. Camel CYP2E1 has higher drug binding power. Camel CYP2E1 more efficiently bound with small compounds. Higher evolution rate and potent chemicals and toxins binding is a form of camel adaptation. Abstract: Camels are raised in harsh desert environment for hundreds of years ago. By modernization of live and the growing industrial revolution in camels rearing areas, camels are exposed to considerable amount of chemicals, industrial waste, environmental pollutions and drugs. Furthermore, camels have unique gene evolution of some genes to withstand living in harsh environments. In this work, the camel cytochrome P450 2E1 (CYP2E1) is compromised to detect its evolution rate and its power to bind with various chemicals, protoxins, procarcinogens, industrial toxins and drugs. In comparison with human CYP2E1, camel CYP2E1 more efficiently binds to small toxins as aniline, benzene, catechol, amides, butadiene, toluene and acrylamide. Larger compounds were more preferentially bound to the human CYP2E1 in comparison with camel CYP2E1. The binding of inhalant anesthetics was almost similar in both camel and human CYP2E1 coinciding with similar anesthetic effect as well as toxicity profiles. Furthermore, evolutionary analysis indicated the high evolution rate of camel CYP2E1 in comparison with human, farm and companion animals. The evolution rate of camel CYP2E1 was among the highest evolution rate in a subset of 57 different organisms. These results indicate rapid evolution and potent toxin binding power of camel CYP2E1.